PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOW BALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 019 SEKELADI - Wahidah Wahidah; Edddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of the problem in this research was carried out because of the low of IPS study result of fourth grader of SD Negeri 019 Sekeladi, with the average class 67,78. Minimum Criteria of Completeness (KKM) IPS is 70. Among students who numbered 20 people only 7 people are complete. The formulation of the problem "Will the implementation of the Snow Ball Throwing Cooperative learning model can improve the learning outcomes of IPS fourth graders Elementary School Elementary School 019 Sekeladi Tanah Putih? This research was conducted on March 20, 2017 until April 10, 2017. The subjects of this study are the fourth graders of SD Negeri 019 Sekeladi with a total of 20 students consisting of 9 men and 11 women. Instrument of data collection in this thesis is observation sheet of teacher and student activity and learning result. The result of research of teacher activity in learning process in first cycle of first meeting was obtained by average value 62.5% and second meeting increased to 70.83% In cycle II first meeting 75% and second meeting increased to 87.5%. The result of data analysis of student activity on first cycle of first meeting 54.16% and second meeting increased to 66.66%. In the second cycle of the first meeting 75% and the second meeting increased to 87.5%. Based on the results of data analysis, the average learning outcomes before the action is an average of 53.5 (less categories). After the action increases in cycle I with average to 66.75 (enough category). In the second cycle increased by an average to 75.75 (good category). Means that the application of the model of Co-operative Type Snow Ball Throwing can improve the learning outcomes of IPS fourth graders of State Elementary School 019 Sekeladikecamatan Tanah Putih.Key Words : Model Learning of Problem Based Instruction ( PBM ) , fourthgraderes Students Achievement